Dark academia : how universities die - Fleming, P. (Peter), 1972- (Pluto Press, 2021)
Bestselling author Peter Fleming uncovers the dark underbelly of the modern university to reveal cracks in the ivory tower.
Keywords: Universities and colleges.; Neoliberalism.; Universities and colleges -- Faculty -- Psychology.; Universités.; Néo-libéralisme.; Universités -- Corps enseignant -- Psychologie.; universities (institutions); colleges (institutions); BUSINESS & ECONOMICS -- General.; Neoliberalism; Universities and colleges; Universities and colleges -- Faculty -- Psychology; Electronic book.